Engineered "coffee-rings" of reduced graphene oxide as ultrathin contact guidance to enable patterning of living cells. Issue 5 (7th March 2019) - Kang, Seok Hee; Shin, Yong Cheol; Hwang, Eun Young; Lee, Jong Ho; Kim, Chang-Seok; Lin, Zhiqun; Hur, Seung Hyun; Han, Dong-Wook; Hong, Suck Won
Abstract : The generation of ultrathin nanotextured films in the form of micropatterns ( i.e., concentric gradient rGO coffee rings) is effectively tailored, and these patterned rGO arrays can be utilized as promising cell-responsive templates. Abstract : Graphene, a two-dimensional (2D) carbon nanomaterial, has received great attention owing to its advantageous characteristics, including superior electrical, chemical and physical properties. In particular, exfoliation of graphite with strong oxidants has been explored to prepare a suspension of individual 2D graphene oxide (GO) nanosheets dispersed in various types of solvents. This colloidal suspension can readily be employed in a wide range of promising potential applications. However, one major challenge is to assemble such individual nanosheets on defined areas of surfaces forming specific structures. Here, we developed a simple and robust one-step strategy to create highly regular ordered nanostructures composed of chemically reduced graphene oxide (rGO) nanosheet building blocks on SiO2 /Si or glass substrates over large areas. An aqueous suspension of rGO nanosheets dispersed in a volatile solvent was subjected to a confined geometry to induce a spontaneous formation of rGO patterned arrays with unprecedented regularity by utilizing both a controlled coffee ring effect and consecutive stick-slip motions of rGO solutions during the drying process. As a result, the generation of ultrathin nanotextured films in the form of micropatterns ( i.e., concentric gradient rGO coffee rings) was effectively tailored. As a biological approach, to fully utilize patterned rGO associated with the nanoscale surface topography, we used these patterned rGO arrays as a biomimetic in vitro architecture to study interfacial interactions of living cells such as fibroblasts, myoblasts, and neuronal cells. The observed results show that the patterned rGO arrays can be used as manipulated cellular responsive templates to form living cell assemblies and related patterns that are useful for regenerative tissue engineering.